Review of Agrenia Börner, 1906 with descriptions of four new species from North America (Collembola, Isotomidae) - Fjellberg, Arne; Bernard, Ernest C. (Zootaxa, 2009)
The eight known species of Agrenia are reviewed and new distributional data are added. Two species groups are suggested for the genus: a bidenticulata-group with a mucronal seta and an agilis-group without a mucronal seta. Four new species of the second group are described from North America: A. falcula, A. parkeri, and A. tarashchukae from forest streams of the Appalachian Mountains in Tennessee, North Carolina, and New York, and A. extrema from glaciers in Washington and Alaska. The head of the maxilla is introduced as a useful character for separation of some species. A key to all species is given.